Revisit Intention Regression Model of Agritourism Destinations of Pelaga and Buyan-Tamblingan, Bali, Indonesia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This investigation was driven in Pelaga and Buyan-Tamblingan Area was organized using a research study that about 500 respondents for the start of 2020 and dictated by an accidental sampling method. The statistical analysis uses multiple linear regression, ANOVA, and R square to make an investigation conclusion. Main findings are simultaneously predictors variables consisting of beautiful scenery, most recently facilities, unique attractions, completeness of facilities, close distance, easy transportation, easy to reach location, and community hospitality significantly influence variable dependent intention to visit with influence strength of the determinant value at 0.539 or 53.9%. This study will enable the marketing practitioners to better understand the motivation of visitors to visit agritourism areas. Some predictor variables that significantly influence the intention to visit are the latest facilities, unique attractions, easy to reach location, and community hospitality.